Psychological Distress and Sources of Stressors amongst Medical and Science Undergraduate Students in Malaysia - Radeef, Ali S; Faisal, Ghasak G (Makara Journal of Health Research, 2017)
Background: This study aims to compare the prevalence of psychological distress between medical and science undergraduate students and to assess the sources of stressors that are attributing to it. Methods: A sample of 697 undergraduate students participated in this study, in which 501 were medical students and the remaining 196 were Science students. Psychological distress was assessed using the 12-item General Health Questionnaire. The students were given a list of possible sources of stress which were chosen depending on previous studies. Results: The overall prevalence of psychological distress was 32.6%. Science students showed a significantly higher rate and mean score of psychological distress than medical students, and the mean score was significantly higher during the clinical phase rather than the pre-clinical phase in medical students. Overall, female students had a significantly higher mean score than males, however although the mean score was higher in females it was only significant in the pre-clinical phase. In addition to academic and psychological stressors, factors such as reduced holidays, lack of time for relaxation, and limitation of leisure/entertainment time were among the top ten stressors reported by the students. Conclusions: Psychological distress is common among university students, and it is higher among science students than medical students. Academic and psychological factors can be considered as sources of stressors which may precipitate psychological distress among college students.